Corporate Governance On Boardroom And Firm Performance: Family-Controlled Company - Choong, Wei Lim (2022)
Purpose: The purpose is to investigate the influences of boardroom towards firm performance among family-controlled listed companies on Bursa Malaysia. Board size, number of independent directors, CEO duality, audit committee size, and number of women directors have been selected as independent variables whereas firm financial performances of the companies known as the dependent variables and were measured by return on asset and return on equity. Design/Methodology/Approach: In this research study, 43 number of familycontrolled companies have been selected from the. A software Statistical Package for Social Science (SPSS) has been used to run the descriptive analysis and was illustrated in table, measurements, and summaries. Besides, EViews also been used to run the panel data analysis. Findings: The result showed the board size has a significant relationship with the family-controlled companies’ financial performance in term of return on asset and equity. Interestingly, there were four independent variable was insignificant to the firm’s financial performance which are number of independent directors, CEO duality, audit committee size and number of women directors. Research Limitation: There might be other potential financial ratio that could be used to measure the firm’s financial performance. Besides, limited time and resources give to conduct in this study, hence the company observation time-period were only 5 years and only 43 number of the companies being selected. This would possibly reduce the accountability and reliability of the analysed results. In addition, this research only used secondary data, which is annual report to run analysis, hence the data shows in the annual report has the possibility of not being accountable Originality/Value: This research able to contribute the theoretical knowledge and development practices to the shareholders or investors, stakeholders, policymakers, as well as academia. This research able to provide investment idea to shareholders XIII and investors. Also, policymakers can better understand the factors that influence the firm performance and develop more comprehensive policy in order to sustain the business operation of family-controlled companies. Besides, policymakers also able to develop comprehensive police to safeguard the interest of Malaysian investors. Lastly, this research also provides insight of corporate governance on board and family-controlled company performance to academic to conduct their research in the future.